Interfacial Exchange Phenomena Driven by Ferromagnetic Domains. Issue 21 (24th June 2022) - Díez, José Manuel; Cuñado, José Luis F.; Lapa, Pavel; Solís, Raúl; Arnay, Icíar; Pedraz, Patricia; Perna, Paolo; Bollero, Alberto; Miranda, Rodolfo; Schuller, Ivan K.; Camarero, Julio
Abstract: Interfacial proximity effects in antiferromagnetic/ferromagnetic (AFM/FM) bilayers control the exchange‐bias (EB) phenomena exploited in most spintronic devices, although still is lack of full understanding. Discordant results, including different exchange‐bias field ( H E ), coercivity ( H C ), or blocking temperature ( T B ) found even in similar systems, are usually ascribed to uncontrolled parameters, namely dissimilar interfacial defects, structure, and thicknesses. Here, it is shown in the very same sample that the magnetic domain structure during the magnetization reversal of the FM layer controls those mentioned effects. Simultaneous transport and vectorial‐resolved magnetic measurements performed in a V2 O3 /Co system during warming after different field cooling (FC) procedures exhibit a strong dependence on the FC angle and the domain structure of the FM layer. Remarkably, magnetization reversal analysis reveals 35 K of variation in T B and up to a factor of two in H E . These observations can be explained within the random‐field model for the interfacial exchange coupling with a fixed AFM domain structure in contact with a variable (angle‐dependent) FM domain structure. The results highlight the importance of the domain structure and magnetization reversal of the FM layer (not previously considered) in the EB phenomena, with potential to tailor interfacial effects in future spintronic devices. Abstract : Interfacial exchange phenomena driven by ferromagnetic domains are shown. The key role of the ferromagnetic texture during reversal in antiferromagnetic/ferromagnetic systems with tailored magnetic anisotropy configuration is revealed from simultaneous magnetic and transport measurements, which provides a new general insight on exchange bias phenomena and opens a new path to develop future spintronic applications.